METHODS OF ORGANIZING SPECIAL STRENGTH TRAINING FOR YOUNG SHORT-DISTANCE RUNNERS IN A ONE-YEAR TRAINING MACROCYCLE - Yuanquan, Pan; Khorshidhmed, H.S.; Vrublevskiy, E.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and substantiate a methodology for organizing special strength training for short-distance runners aged 14-15 years in an annual training cycle. Methods and structure of the study. The experiment involved young sprinters training at the sports school in Al-Diwaniya (Iraq). An experimental group (EG, n=13) was formed, classes in it were conducted on the basis of the author's methodology for organizing special strength training for sprinters in a yearly cycle, and a control group (CG, n=15), which trained according to the program generally accepted in Iraq for this contingent . Results and conclusions. The results of an experimental verification of the developed methodology for organizing special strength training for short distance runners aged 14-15 years in the annual training cycle are presented. The data obtained testify to the productivity of this technique, as well as the content of the normative indicators that assess the readiness of young sprinters.